Risk of admission requirement among children with respiratory infection in the post-COVID-19 pandemic era - Takahiro Mori; Taito Kitano; Daisuke Kitagawa; Masayuki Murata; Mai Onishi; Soshi Hachisuka; Tenshin Okubo; Naohiro Yamamoto; Hiroki Nishikawa; Masayuki Onaka; Rika Suzuki; Madoka Sekine; et al. (Journal of Infection and Public Health)
Background: To evaluate the effect of the type and codetection of respiratory viruses on admission requirements among children with respiratory infections in the post-COVID-19 pandemic era. Methods: In this retrospective study, we analyzed patients with acute respiratory symptoms using FilmArray® Respiratory Panel between December 2020 and March 2024. The viruses were classified into eight groups: adenovirus, seasonal coronavirus, human metapneumovirus, human rhinovirus/enterovirus, influenza virus, parainfluenza virus, respiratory syncytial virus, and severe acute respiratory virus coronavirus-2. The impact of the detected viral groups and viral codetection on hospitalization rates were examined using multivariable regression analysis in three pediatric age groups (<2 years, 2–4 years, and 5–17 years). Results: A total of 4684 tests were performed, of which 3555 (75.9 %) tested positive for at least one respiratory virus and negative for atypical bacteria. Of these, 946 (26.6 %) were hospitalized. Multivariable regression analyses showed that respiratory syncytial virus (RSV) infection was associated with hospitalization requirement among young children (adjusted odds ratios (aOR) 2.46 [1.65–3.67], p < 0.001 in < 2 years, and 1.34 [1.02–2.30], p = 0.042 in 2–4 years). Influenza (aOR 0.23 [0.07–0.83], p = 0.025) and SARS-CoV-2 (aOR 0.39 [0.22–0.69], p = 0.001) were negatively correlated with hospitalization among children younger than 2 years. Viral codetection was not significantly associated with hospitalization in any pediatric age group. Conclusion: RSV infection was associated with a higher risk of hospitalization in children younger than 5 years than other respiratory viruses. These results highlight the importance of preventive measures against RSV infections, including maternal vaccination and childhood immunization.